Analisis Strategi Pengembangan Usaha Bank Sampah Garuda Wastu Lestari - Putri Anggreni (Universitas Mahendradatta Denpasar, 2018)
Research conducted at Waste Bank Garuda Wastu Lestari is located in the Peguyangan Village, Denpasar was done in order to analyze the environmental factors that affect the internal and external business development of waste bank and formulate alternative strategies that can be applied by Waste Bank Garuda Wastu Lestari. Determination of respondent committed intentionally with a specific purpose (pusposive sampling). Respondents in this study consisted of four respondents from the management company. Questionnaires conducted to analyze the internal and external environment. Determination of strategic alternatives conducted using SWOT Matrix and prioritization strategy that can be applied at this time adapted to the position of Waste Bank Garuda Wastu Lestari in the competition. SWOT analysis of the diagram looks that the company is in cell 1, in the cell Aggressive Strategy. While the outcome of the preparation through the SWOT Matrix are eleven alternative strategies that can be applied by Waste Bank Garuda Wastu Lestari. Priority strategy selection can be done by looking at the company's position in the current competition is with Strategy SO (Strength-Opportunity), utilizing the strength to seize the opportunities that exist. Thus the right business priorities do is: 1) to maintain and improve the quality of care produced; 2) maintain and enhance good relations with employees, customers, and the agency or agencies; 3) maintain and improve the promotion and dissemination activities; and 4) improve cooperation and networking of waste bank.